APPLICATION OF TOTAL-REFLECTION X-RAY FLUORESCENCE SPECTROMETRY (TXRF) TO GEOLOGICAL OBJECTS: EXPERIENCE OF THE TXRF LABORATORY, CENTER FOR GEODYNAMICS AND GEOCHRONOLOGY - A. S. Maltsev; G. V. Pashkova (Геодинамика и тектонофизика)
Unlike conventional X-ray fluorescence spectrometry, the total-reflection X-ray fluorescence spectrometry is not a widespread and routine method for analyzing solid samples with mineral matrix, but it has a great potential for geochemical, geological, and archaeological studies. Rapid multi-elemental analysis of very small sample amounts can be performed by the internal standard method which does not require the matrix-matched reference materials. This is an undoubted advantage of the TXRF method over the conventional X-ray fluorescence method, especially if there is a limited available sample amount and a lack of well-characterized reference materials. This paper presents our experience with the application of TXRF spectrometry in the elemental analysis of apatite, ceramics, sediments, ores, and nodules. Special attention has been paid to the sample preparation procedure because it is one of the main sources of errors in the analysis. Preparing thin homogeneous specimen from the solid sample with a complex mineral matrix is not easy. Sample preparation strategy should be chosen considering the features of an analytical object, the content of the elements to be determined, and the accuracy required for a reliable interpretation. Consideration is being given to the examples of the preparation of a suspension for rapid analysis of ores and sediments, and to the original techniques of chemical decomposition for apatite and ceramics.